Measuring Undergraduate Students' Construction Education Domain Self-Efficacy, Motivation, and Planned Behavior: Validation of a Concise Survey Instrument. Issue 4 (2nd October 2018) - Elliott, Jonathan W.; Perkins, Mark; Thevenin, Melissa K.
ABSTRACT: Reducing attrition in education and training is an important strategy for addressing unmet U.S. construction industry workforce demands. This study investigated the psychometric properties of a more concise construction-domain specific survey instrument, the Construction Training Attitudes and Intentions Scale (CTAIS), using Confirmatory Factor Analysis (CFA). Results yielded an abbreviated 28-item instrument and 4-factor model. CTAIS factors; Construction Education Self-Efficacy (CESE), Motivation (CEM), Planned Effort (CEPE) and Perceived Completion Value (CECV) were tested for convergent, discriminant, and known-groups validity. Exploratory Factor Analysis (EFA) was conducted initially to confirm the instrument's factor structure. CFA was employed to compare the hypothesized four-factor model to a single-factor model; fit indices were acceptable with nine items removed given discrepancies. Based on the demonstrated instrument reliability and validity, the abbreviated CTAIS provides a useful quantitative metric that can be completed quickly by participants while still assessing the constructs shown to predict education performance and attrition within the specific domain of construction training and education.